Analisis Pengaruh tingkat Pendidikan dan tingkat upah terhadap angka pengangguran terbuka di Sumatera Utara 2020-2022 - hariyatih, Suri; Khairani, Zahra Amalia; Ritonga, Fitri (Universitas Muhammadiyah Enrekang, 2024)
This research will look at how the minimum wage and educational attainment affect the level of open unemployment (case study in North Sumatra province) in the period 2020 to 2022. The multiple linear regression analysis method is applied in quantitative research methodology. Secondary data from the North Sumatra Province Central Statistics Agency was used as the data source. This method revealed that a negative relationship between wage levels and education levels was found on the unemployment rate, which means that when the two variables discussed increase, the open unemployment rate will actually decrease. This shows the need to increase wage levels and education levels in North Sumatra in order to reduce the level of open unemployment regionally.